Atypical presentation of genital molluscum contagiosum mimicking genital warts. (December 2020) - Kumar, Sheetanshu; Aggarwal, Divya; Chatterjee, Debajyoti; Vinay, Keshavamurthy
A man in his 20s with a history of unprotected sex with a commercial sex worker three months before presented with a solitary slowly-growing, well-defined, non-tender, oval, verrucous lesion on the mucosal aspect of his prepuce. Dermoscopy revealed a polylobular, pinkish-white, amorphous structure in the centre with a surrounding crown of vessels that did not cross the centre of the lobules, and histopathology showed keratinocytes containing intracytoplasmic faintly granular eosinophilic inclusions and peripherally-pushed nuclei. A diagnosis of agminated genital molluscum contagiosum was reached on the basis of the above findings. Molluscum contagiosum can present with several atypical morphologies mimicking other dermatoses. Agminated molluscum contagiosum can closely mimic a genital wart especially if it is involving the ano-genital region. Awareness among clinicians regarding the atypical presentations of molluscum contagiosum is imperative for early diagnosis and management of this infectious condition.